Synthesis of (E)-1-(2,4-Bis((1-phenyl-1H-1,2,3-triazol-4-yl)methoxy)phenyl)-3-phenylprop-2-en-1-one Derivatives and their Antimicrobial Activity - Umapathi, Nalla; Jalapathi, Pochampally; Raghavender, Matta; Shankar, Bhookya (Asian Journal of Chemistry, 2021)
A new series of chalcone based bis 1,4-disubstituted 1,2,3-triazole heterocyclic molecules (6a-j) were synthesized via the reaction of 1-(2,4-bis((1-phenyl-1H-1,2,3-triazol-4-yl)methoxy)phenyl)ethanone (6a-e) with substituted benzaldehyde. All the molecules were characterized by IR, 1H and 13C NMR and MS spectra spectral data. Compounds 6a-j were evaluated for their antimicrobial effects using a broth disc diffusion method. The compounds were evaluated for their in vitro antimicrobial potential against Gram-positive (Micrococcus luteus, Methicillin-resistant Staphylococcus aureus, Bacillus subtilis and Bacillus cereus), Gram-negative (Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli and Proteus vulgaris) bacterial and fungal (Microsporum canis, Microsporum gypseum and Epidermophyton floccosum) strains by comparison of the reference drugs, zentamycin sulphate (antibacterial) and nystatin (antifungal). The screened compounds 6f, 6e, 6c and 6i were found to be the most active against all the tested bacterial and fungal strains.